2020
DOI: 10.1002/vms3.379
|View full text |Cite
|
Sign up to set email alerts
|

First case report on the occurrence of Trypanosoma evansi in a Siam B Mare in Kelantan, Malaysia

Abstract: This is the first case report for the positive Trypanosoma evansi incident in Kelantan, Malaysia confirmed through protozoa detection in a Siam B mare. The horse was presented with complaints of lethargy and inappetence and it collapsed on the day of visit. Normal saline and dextrose solution were administered intravenously, while multivitamins and nerve supplements were given intramuscularly to stabilise the horse before further treatment. Haematological findings showed normocytic hypochromic anaemia and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…Hematological examinations of the T. evansi infected horses showed that the horses had normocytic and hypochromic anemia, whereas horses infected with T. vivax suffered from normocytic normochromic anemia. These results agree well with previous studies [23,24]. In fact, anemia can be considered the most important and main sign of trypanosomiasis, which is closely related to the degree of parasitism.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hematological examinations of the T. evansi infected horses showed that the horses had normocytic and hypochromic anemia, whereas horses infected with T. vivax suffered from normocytic normochromic anemia. These results agree well with previous studies [23,24]. In fact, anemia can be considered the most important and main sign of trypanosomiasis, which is closely related to the degree of parasitism.…”
Section: Discussionsupporting
confidence: 93%
“…vivax. The clinical findings observed in this study were consistent with those reported in previous studies in horses infected with T. evansi, such as fever, anemia and hindquarter weakness, lethargy, staggering gait, incoordination, and ataxia [23,24]. Hematological examinations of the T. evansi infected horses showed that the horses had normocytic and hypochromic anemia, whereas horses infected with T. vivax suffered from normocytic normochromic anemia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation